Computational methods in Dirichlet-Neumann coupling of soil-structure interaction - Zolghadr,Jahromi H; Izzuddin,BA; Zdravkovic,L (2008)
This paper presents domain decomposition methods for nonlinear analysis of soil-structure interaction problems, where particular emphasis is given to Dirichlet-Neumann iterative coupling methods. In this approach, the overall soil-structure domain is physically decomposed into independently modelled soil and structure sub-domains, and then the response of separately modelled sub-domains is coupled by successive updates of the boundary conditions, ensuring convergence to equilibrium and compatibility at the interface of the soil-structure coupled system. In this respect, the mathematical and computational characteristics of using constant relaxation, adaptive relaxation and condensed stiffness matrix of the partitioned sub-domains in coupling algorithms are discussed, including the convergence conditions and choice of algorithmic parameters. In view of the above, the use of a modified reduced order method, which utilises an efficient approximation of the condensed stiffness matrices at the soil-structure interface to ensure and accelerate convergence, is discussed and its merits are illustrated in a case study. © 2009 Taylor & Francis Group, London.